Evolution of groundwater recharge as a result of forest development on the east coast of the province of Buenos Aires, Argentina - Carretero, Silvina Claudia (2021)
Changes in groundwater recharge associated with variations in land use were analysed with a focus on the role of afforestation on the east coast of Buenos Aires, Argentina. The growth of the population related to such changes was considered, linking water consumption to variations in recharge. A multi-temporal analysis was carried out using aerial photographs for the years 1957, 1975, 1981 and 2016, differentiating three types of cover: bare soil, forested soil and grassland. Water balances for each type of land use and groundwater recharge were estimated. In the forested soil, a reduction in recharge over time can be observed and it can be appreciated that forest expansion occurs at the expense of the sand-dune area, which offers the greatest possibilities for infiltration. At present, the water consumption, which depends solely on the groundwater reserves, is lower than the recharge, but this relationship is reversed during the tourist season. According to the estimated projections, the drinking water supply would be compromised in the coming decades, reaching a critical point or level of collapse as from 2070. This proves that it is essential for the policies and projects aiming at afforestation for different purposes to take into consideration the role of this change in land use when assessing the sustainability of the associated water resources.